PENINGKATAN HASIL BELAJAR PRAKARYA DAN KEWIRAUSAHAAN MELALUI TEAM GAMES TOURNAMENT LEARNING (UNO STACKO CHALLENGE) - Neni Hendaryati (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
The purpose of this study was to determine the improvement of craft and entrepreneurship learning outcomes (PKWU) students of class XI IPS Jatibarang 1 High School through a team game tournament learning (uno stacko challenge). The population was students of class XI totaling 90 people. Sampling uses a cluster sampling technique. Samples were taken as many as 2 classes, one experimental class with 29 students and one control class with 32 students. Data collection methods used are observation, documentation, and tests. The test instruments were using validity, data reliability, difficulty level and different test, while the hypothesis test used t-test assisted by SPSS program. The descriptive analysis calculation states that the average learning class completeness in the experimental class increased by 34.4% compared to the previous one. Significance on Levene’s Test shows a number of 0.071 this means normal and homogeneous data. While the significance value (2-tailed) is known to be 0,000 with a significance level of 5%, it can be said that the hypothesis that the team games tournament learning with uno stacko challenge games is effectively implemented in order to improve craft learning outcomes and entrepreneurship is acceptable. In an effort to improve education, especially in the learning process, teachers must be able to apply various learning models. The goal is that students are more active, can cooperate, practice concentration and be able to solve learning problems so that the learning outcomes of each subject also increase. Principals as policy makers at the lowest level participate to help improve teacher competency through the provision of training learning models and the use of media as a learning tool.Keyword: Team Games Tournament, Uno Stacko, Study Result